Intra-annual stem radial increment patterns of Chinese pine, Helan Mountains, Northern Central China - Gao, Jiani; Yang, Bao; He, Minhui; Shishov, Vladimir (Trees-Structure and Function, 2019)
Key messageWe investigate the intra-annual growth patterns of Chinese pine in Helan Mountains, confirming that regional water status plays a dominated role in stem radial increment.AbstractThe associations between environmental conditions and stem radial increment (SRI) are useful for assessing a species' growth response to climate change. Intra-annual SRI dynamics of Chinese pine (Pinus tabulaeformis) were monitored half-hourly by automatic point dendrometer during the growing season (May-September) in 2016 and 2017 at two altitudes in the Helan Mountains, northern central China. Here, we compared the seasonal growth patterns between two altitudes and 2 years. Trees at low altitude are characterized by earlier cessation, shorter growing season, and lower growth rate, resulting in less annual growth, which may reflect the greater drought intensified by rising temperature at low altitude. June precipitation significantly affected tree growth rate. The xylem growth was active when daily mean air temperature was 9.9 degrees C at our study region for P. tabulaeformis in an arid environment. During the growing season, daily stem radial increment showed a significantly positive correlation with precipitation and a negative correlation with daily air temperature at all altitudes. Climatic variables associated with tree water status, namely precipitation, vapor pressure deficit, and relative humidity, played important roles in daily stem radial increment as the same result as a linear mixed model. These factors drive the complex physiological processes of stem radial increment by influencing the moisture available to the tree.
CRIS-Team WoS Importer:2019-06-18

New perspective on spring vegetation phenology and global climate change based on Tibetan Plateau tree-ring data. - Yang, Bao; He, Minhui; Shishov, Vladimir; Rossi, Sergio; Vaganov, Eugene; Tychkov, Ivan; Ljungqvist, Frederik; Bräuning, Achim; Grießinger, Jussi (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Phenological responses of vegetation to climate, in particular to the ongoing warming trend, have received much attention. However, divergent results from the analyses of remote sensing data have been obtained for the Tibetan Plateau (TP), the world's largest high-elevation region. This study provides a perspective on vegetation phenology shifts during 1960-2014, gained using an innovative approach based on a well-validated, process-based, tree-ring growth model that is independent of temporal changes in technical properties and image quality of remote sensing products. Twenty composite site chronologies were analyzed, comprising about 3,000 trees from forested areas across the TP. We found that the start of the growing season (SOS) has advanced, on average, by 0.28 d/y over the period 1960-2014. The end of the growing season (EOS) has been delayed, by an estimated 0.33 d/y during 1982-2014. No significant changes in SOS or EOS were observed during 1960-1981. April-June and August-September minimum temperatures are the main climatic drivers for SOS and EOS, respectively. An increase of 1 °C in April-June minimum temperature shifted the dates of xylem phenology by 6 to 7 d, lengthening the period of tree-ring formation. This study extends the chronology of TP phenology farther back in time and reconciles the disparate views on SOS derived from remote sensing data. Scaling up this analysis may improve understanding of climate change effects and related phenological and plant productivity on a global scale.